An Innovative Fluorescent Semi-quantitative Methylation-specific PCR Method for the Determination of MGMT Promoter Methylation is Reflecting Intra-tumor Heterogeneity - Nguyen, Aurelia; Legrain, Michele; Noel, Georges; Coca, Andres; Meyer Ea, Nicolos; Schott, Roland; Lasthaus, Christelle; Chenard, Marie Pierrette; Gaub, Marie Pierre; Lessinger, Jean Marc; Guenot, Dominique; Entz-Werle, Natacha (Current cancer drug targets, 2015)
High grade gliomas (HGG) are usually associated with a very dismal prognosis, which was moderately improving in the last decade with the introduction of the alkylating agent temozolomide in their treatment. The methylation status of MGMT (O6 methylguanine DNA-methyltransferase) promoter is one of the strongest predictive and prognostic factors for the patient chemoresponse. For instance, the molecular method of assessment for MGMT promoter status is not standardized. In this background, we developed a fluorescent capillary gel electrophoresis-based methylation specific-PCR. This technique allowed a semi-quantitative estimate of the relative ratio between methylated and unmethylated alleles. The efficacy and accuracy of the technique was assessed in a retrospective cohort of 178 newly diagnosed adult HGGs, who were homogeneously treated. First, we analyzed the impact on survival of different cut-off points in the MGMT promoter methylation and, to go further, we correlated these different rates to other well-known prognostic molecular factors involved in adult HGGs. This strategy allowed to validate our technique as a very sensitive technique (detection of a low methylation percentage, < 5%), which was feasible in fresh-frozen as well as in FFPE samples and had the propensity to detect intra-tumor heterogeneity. This technique identified a new sub-group of anaplastic oligodendrogliomas or oligoastrocytomas defined by a minor methylation and a worse outcome and, therefore, will help to substratify accurately into more homogeneous subgroups of methylated tumors.